PENGGUNAAN AI DALAM PROSES PEMBELAJARAN MAHASISWA MAGISTER ILMU KOMUNIKASI KELAS BEASISWA KOMINFO UNIVERSITAS SUMATERA UTARA - M. Aidil Hariyandi; Saputra, Dian; Simamora, Monojaya; Pohan, Syafruddin (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2025)
This research will discuss how the transformation of AI-based technology (artificial intelligence) affects the learning process among master students. The research method used is descriptive qualitative by taking a case study among students receiving the Kominfo scholarship. Data were collected through interviews, observation, and documentation. Interviews were conducted using purposive sampling technique, namely students who received Kominfo scholarships. The results of this study show that the use of AI in learning helps students to complete various lecture assignments. Various AI features used include virtual assistants, chatboxes, and social media data analysis. However, there are challenges faced in the form of knowledge gaps and tendency to depend on the use of technology that reduces the ability to think critically and independently.